2011
DOI: 10.1111/j.1439-0507.2011.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of sodium hypochlorite and chlorhexidine digluconate in clinical isolates of Sporothrix schenckii

Abstract: The susceptibility of Sporothrix schenckii isolates from clinical cases of canine, feline and human sporotrichosis, and from the environment, was evaluated with 4% sodium hypochlorite and 6.6% chlorhexidine digluconate using the broth microdilution, agar diffusion and direct exposure techniques. The minimal inhibitory concentration was smaller than 0.8% for chlorhexidine digluconate and between 8% and 4% for sodium hypochlorite. Inhibition zones were not found in agar diffusion for sodium hypochlorite, and zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The poor performance of the sodium hypochlorite in broth microdilution and disk diffusion tests was similar to that found in a study that evaluated the performance of the chlorhexidine digluconate and sodium hypochlorite in isolates of S. schenckii (Madrid et al, 2012). In a trial evaluating the efficacy of disinfectants in bacteria using the disk diffusion technique, the 0.5% chlorhexidine was effective, while sodium hypochlorite only had bactericidal activity at concentrations of 2% or more (Pedrini and Margatho, 2003).…”
Section: Speciessupporting
confidence: 72%
See 2 more Smart Citations
“…The poor performance of the sodium hypochlorite in broth microdilution and disk diffusion tests was similar to that found in a study that evaluated the performance of the chlorhexidine digluconate and sodium hypochlorite in isolates of S. schenckii (Madrid et al, 2012). In a trial evaluating the efficacy of disinfectants in bacteria using the disk diffusion technique, the 0.5% chlorhexidine was effective, while sodium hypochlorite only had bactericidal activity at concentrations of 2% or more (Pedrini and Margatho, 2003).…”
Section: Speciessupporting
confidence: 72%
“…Chlorhexidine digluconate was effective against dermatophytes in lower values of MIC and MFC (4.16 μL/mL). Similar research using this disinfectant at 66.7 μL/mL against clinical and environmental isolates of Sporothrix schenckii, dimorphic fungus, obtained inhibitory effect at concentrations below 0.8% (Madrid et al, 2012). The efficacy of chlorhexidine at 4.16 μL/mL was previously demonstrated in filamentous fungi of the genera Aspergillus (Xavier et al, 2007;Xavier et al, 2008) and using a 1% aqueous solution of chlorhexidine against yeasts for the disinfection of surfaces using the technique spray wipe spray (Bambace et al, 2003).…”
Section: Speciessupporting
confidence: 59%
See 1 more Smart Citation
“…18 This was attributed to a reaction of the biocide with the organic material. Since how well an antimicrobial diffuses through the agar medium is critical and proportional to zone size observed 7,10,11 , reactions with organic materials (protein components) 17,18 in the nutrient agar may help explain why sodium hypochlorite produced relatively small zones in this study (as shown in Figures 1a and 1b) compared to the above studies which utilized different agar types. Binding to organic/protein components has also been shown to be an issue affecting the antimicrobial activity of quaternary ammonium compounds (QACs) such as benzalkonium chloride.…”
mentioning
confidence: 99%
“…7,8 Another explanation may involve the dependence of the antimicrobial effectiveness of sodium hypochlorite on pH. 18,19 Madrid et al 18 stated that more alkaline pH results in longer stability of hypochlorite solutions. Therefore the acid pH of the nutrient agar used in this study may have resulted in instability of the biocide and hence a negative effect on its antimicrobial efficacy.…”
mentioning
confidence: 99%